Can a maize price band work in Malawi? - Baulch, Bob; Botha, Rosemary (International Food Policy Research Institute, 2020)
Price band schemes have been used in many countries to try and set minimum and maximum prices between which staple food prices vary. This is typically done using a buffer stock scheme, which sells grain from a reserve when retail prices are higher than a pre-determined ceiling price and buys grain to store in the reserve when prices fall below a pre-determined floor price. Malawi has attempted to stabilize the price of its main staple, maize, for many years. Since 1999, this has been the dual responsibility of the National Food Reserve Agency (NFRA), which manages the nation’s Strategic Grain Reserve, and the Agricultural Marketing and Development Corporation (ADMARC), an agricultural marketing parastatal with an extensive network of depots and warehouses throughout the country. The precise division of responsibilities for maize price stabilization between the NFRA and ADMARC is unclear, although it is ADMARC which has the mandate to buy from farmers and sell to consumers while NFRA’s principal role is to manage the Strategic Grain Reserve. This note updates previous IFPRI analysis which examined, based on historical maize prices, how often ADMARC would need to intervene in different markets to defend a plausible range of ceiling and floor prices. The floor price corresponds to the minimum farmgate price announced by the Ministry of Agriculture and Food Security (MoAFS) at the beginning of each harvest season while the ceiling price corresponds to the sales price of maize at ADMARC depots. The price band is then the gap between the floor and ceiling price. To defend a set floor price, ADMARC would need to buy off any excess supply on the market, thereby creating an upward pressure on maize prices. Conversely, to ensure the ceiling prices are not exceeded, the NFRA would need to release maize for ADMARC to sell on the market to create a downward pressure and bring the prices down to the ceiling price. International experience indicates that defending floor/ceiling prices in all circumstances is a very expensive proposition.